Knowledge of Stroke Risk Factors and Warning Signs in Patients with Recurrent Stroke or Recurrent Transient Ischaemic Attack in Thailand - Jittima Saengsuwan; Pathitta Suangpho; Somsak Tiamkao (Neurology Research International)
Stroke is a global burden. It is not known whether patients who are most at risk of stroke (recurrent stroke or recurrent transient ischaemic attack) have enough knowledge of stroke risk factors and warning signs. The aim of this study was to assess the knowledge of stroke risk factors and warning signs in this high-risk population. We performed a cross-sectional questionnaire-based study of patients with recurrent stroke or recurrent TIA admitted to Srinagarind Hospital and Khon Kaen Hospital, Thailand. A total of 140 patients were included in the study (age 65.6±11.3 years [mean ± SD], 62 females). Using an open-ended questionnaire, nearly one-third of patients (31.4%) could not name any risk factors for stroke. The most commonly recognized risk factors were hypertension (35%), dyslipidemia (28.6%), and diabetes (22.9%). Regarding stroke warning signs, the most commonly recognized warning signs were sudden unilateral weakness (61.4%), sudden trouble with speaking (25.7%), and sudden trouble with walking, loss of balance, or dizziness (21.4%). Nineteen patients (13.6%) could not identify any warning signs. The results showed that knowledge of stroke obtained from open-ended questionnaires is still unsatisfactory. The healthcare provider should provide structured interventions to increase knowledge and awareness of stroke in these patients.